Comparative study of rivastigmine and galantamine on the transgenic Drosophila model of Alzheimer's disease - Yasir Hasan Siddique; Falaq Naz; Rahul; Himanshi Varshney (Elsevier, 2022)
Alzheimer's Disease (AD) is characterized as a progressive neurodegenerative disease most commonly associated with memory deficits and cognitive decline. The formation of amyloid plaques and neurofibrillary tangles are important pathological markers of AD. The accumulation of amyloid plaques and neurofibrillary tangles leads to the loss of neurons including the cholinergic neurons thus decreasing the levels of acetylcholine (a neurotransmitter). To reduce the AD symptoms cholinesterase inhibitors are widely used to decrease the hydrolysis of acetylcholine released from presynaptic neurons. In the present study we have studied the effect of rivastigmine and galantamine (commonly used cholinesterase inhibitors) on the transgenic Drosophila model of AD expressing human Aβ-42 in the neurons. The effect of similar doses of rivastigmine and galantamine (i.e. 0.1,1 and 10 ​mM) was studied on the climbing ability, lifespan, oxidative stress markers, caspase 9 and 3, acetylcholinesterase activity and on the formation of Aβ-42 aggregates. The results suggest that the rivastigmine is more potent in reducing the oxidative stress and improving climbing ability of AD flies. Both the drugs were found to be effective in increasing the lifespan of AD flies. Galantamine was found to be a more potent inhibitor of acetylcholinesterase compared to rivastigmine. Galantamine prevents the formation of Aβ-42 aggregates more effectively compared to rivastigmine.